An Ethical Exploration of Privacy and Radio Frequency Identification - Peslak, Alan R. (Journal of business ethics, 2005)
This manuscript reviews the background of Radio Frequency Identification (RFID) as well as the ethical foundations of individual privacy. This includes a historical perspective on personal privacy, a review of the United States Constitutional privacy interpretations, the United Nations Declaration of Human Rights, European Union Regulations, as well as the positions of industry and advocacy groups. A brief review of the information technology ethics literature is also included. The RFID privacy concerns are three-fold: pre-sales activities, sales transaction activities, and post-sales uses. A proposal to address these privacy concerns is detailed, generally based on past philosophical frameworks and specifically on the Fair Information Practices that the Federal Trade Commission has outlined for the electronic marketplace (e-commerce). It is proposed that by application of these Fair Information Practices, the major privacy issues of RFID can be addressed.